2017
DOI: 10.1186/s12931-017-0663-1
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular traps in patients with pulmonary tuberculosis

Abstract: Tuberculosis is a devastating infectious disease causing many deaths worldwide. Recent investigations have implicated neutrophil extracellular traps (NETs) in the host response to tuberculosis. The aim of the current study was to obtain evidence for NETs release in the circulation during human tuberculosis. For this we measured the plasma concentrations of nucleosomes in conjunction with neutrophil elastase, in 64 patients with active pulmonary tuberculosis and 32 healthy controls. Patients with active tubercu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 17 publications
(30 reference statements)
0
19
0
Order By: Relevance
“…[62] Higher KYNA level was reported in tick-borne encephalitis, schizophrenia, and HIV-related illness, and are known to create confusion and psychotic symptoms in humans. [65] Therefore, higher SERPINA1 in circulatory small EVs may provide defense to individuals that carry Mtb by countering infection with the higher NE levels to neutralize bacterial infection and promote neutrophil phagocytosis. Neutrophil elastase (NE) released from white blood cells fight infection and higher serum NE abundance was reported in tuberculosis patients.…”
Section: Discussionmentioning
confidence: 99%
“…[62] Higher KYNA level was reported in tick-borne encephalitis, schizophrenia, and HIV-related illness, and are known to create confusion and psychotic symptoms in humans. [65] Therefore, higher SERPINA1 in circulatory small EVs may provide defense to individuals that carry Mtb by countering infection with the higher NE levels to neutralize bacterial infection and promote neutrophil phagocytosis. Neutrophil elastase (NE) released from white blood cells fight infection and higher serum NE abundance was reported in tuberculosis patients.…”
Section: Discussionmentioning
confidence: 99%
“…These adhesive interactions can form platelet-monocyte aggregates (PMA) and platelet-neutrophil aggregates (PNA) which lead to cell activation and enhance immune function such as cytokine or MMP production. Platelets can stimulate neutrophils to release neutrophil extracellular traps (NETs) ( 69 ), which are increased in the plasma of TB patients ( 70 ) and have been associated with severe TB-associated lung damage and subsequent sequelae ( 71 ). These adhesive interactions are mediated by the two main families of cell adhesion molecules, selectins and integrins.…”
Section: Platelet-leukocyte Signaling and Cellular Interactions In Tbmentioning
confidence: 99%
“…1 Because many of the antimicrobial contents of neutrophil extracellular traps (NETs) have intrinsic cytotoxic activity, they also have the potential to cause bystander injury to host cells. [3][4][5][6] However, more recent work has demonstrated that NETs also form in response to noninfectious tissue injury. [3][4][5][6] However, more recent work has demonstrated that NETs also form in response to noninfectious tissue injury.…”
Section: Introductionmentioning
confidence: 99%
“…2 In the lung, this has been suspected during infectious exacerbations of cystic fibrosis (CF), chronic pulmonary obstructive disease, bacterial pneumonia, and tuberculosis. [3][4][5][6] However, more recent work has demonstrated that NETs also form in response to noninfectious tissue injury. NETs have been reported to promote inflammation in models of primary lung graft dysfunction (PGD), 7 transfusion-related acute lung injury, 8 and ventilation-induced acute lung injury.…”
Section: Introductionmentioning
confidence: 99%